(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the health-related quality of life of patients after kyphoplasty and vertebroplasty at Hospital of Post and Telecommunications and to analyze associated factors. Methods: A cross-sectional descriptive study was conducted on 92 patients with osteoporotic vertebral compression fractures who underwent vertebral body augmentation with bone cement at the General Surgery Department, Hospital of Post and Telecommunications. Each patient’s health-related quality of life was assessed at three time points: before surgery (on admission), before discharge, and 1 month after surgery. The EQ-5D-5L instrument was used to measure health-related quality of life across five dimensions (mobility, self-care, usual activities, pain/discomfort, anxiety/depression), together with the EQ-VAS (0-100 points) for patients to self-rate their current health status. Convenience sampling was applied from February 2025 to Six 2025. Results: The mean EQ-5D-5L index increased from -0.371 (preoperative) to 0.514 (before discharge) and reached 0.913 at one month (p < 0.001). The mean EQ-VAS score increased from 48.8 to 76.2 and 96.0 points, respectively (p < 0.001). The improvement in health-related quality of life was statistically significant across all health dimensions. Analysis of associated factors showed that patients under 70 years of age, those who were still able to walk (even with difficulty) at admission, and those working in informal/self-employed jobs had significantly higher post-operative health-related quality of life scores than the other groups (p < 0.05). Conclusion: Vertebroplasty and kyphoplasty markedly improves the quality of life of patients with osteoporotic vertebral compression fractures, particularly at one-month follow-up. Younger patients, those who retain preoperative mobility, and those who are still working tend to achieve greater health-related quality of life improvement. Greater attention should be paid to postoperative care for elderly patients, those with limited mobility, and those performing heavy labor, along with strengthening rehabilitation, psychological support, nutritional care, and long-term follow-up to maintain treatment effectiveness.